PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN IPS SISWA KELAS VIII.D SMP NEGERI 1 SIMPANG KANAN - ', Mariani; ', Gusnardi; ', R.M Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to increase students' motivation in social studies class of VIII. D SMPN 1 Simpang Kanan, Rokan Hilir through the implementation of learning model of Make A Match on the subject matter even semester in the academic year 2015/2016. The subjects of this study were 20 students consisting of 10 male students and 10 female students. From the research activity of teacher has increased in the first cycle obtained a score of 70.83% both categories, the percentage increased to 95.83% with the category very well. Activities of students in the first cycle only get a percentage 71.67% both categories, increased in the second cycle to a percentage of 86.67% with a good category. Student's motivation is also seen to rise, it is evident from the percentage of student motivation in the first cycle that only earn a percentage of 75.00% in both categories, the percentage increased to 83.75% in both categories. According to the results of the data analysis and discussion of the implementation of this study can be concluded that the use of learning model Make A Match with media cards can increase students' motivation in social studies class VIII D SMPN 1 Simpang Kanan, Simpang Kanan Rokan Hilir in the academic year 2015/2016.Keywords: Make a Match and Motivation.